Dermoscopic approach to inflammatory lesions in skin of color - Balachandra S Ankad; Varsha R Koti (Wolters Kluwer Medknow Publications, 2020)
Introduction: Dermoscopy is an in vivo and non-invasive tool that assists as an adjunctive method in the diagnosis of many dermatoses. Dermoscopic studies and research in the field of inflammatory and infective lesions are limited to case series or case reports without definitive criteria. Authors have attempted to describe a very basic approach to dermoscopic diagnosis of inflammatory conditions like psoriasis, eczema, lichen planus, pityriasis rosea, prurigo nodularis, and discoid lupus erythematosus. Aim: To propose basic dermoscopic guidelines in terms of approach to an inflammatory lesion.Summary: Dermoscopy of inflammatory conditions is referred to as 'inflammoscopy'. Basic approach in inflammoscopy is based on 5 dermoscopic parameters which include; i) background colour, ii) vessels, iii) scales, iv) follicular findings and v) specific clues. Dermoscopy helps in the differentiation of many inflammatory lesions by demonstrating characteristic patterns thus aiding in its diagnosis. Uniform and regular dotted vessels are seen in psoriasis. Wickham striae, adherent fabric fibre sign, yellow clod sign and white rosettes are respectively a special clue for the diagnosis of lichen planus, prurigo nodularis, eczema and early DLE lesion. Collarette scales over brownish yellow background are seen in P. rosea. Dermatologist dealing with skin lesions in patients with skin types IV, V, and VI should be aware that there are slight variations in the dermoscopic pattern owing to amount of melanin.